BMP tests of source selected OFMSW to evaluate anaerobic codigestion with sewage sludge - Cabbai, V.; Ballico, M.; Aneggi, E.; Goi, D.
The aim of this study is to characterize different types of source selected organic fraction of municipal solid waste (SS-OFMSW)in order to optimize the upgrade of a sewage sludge anaerobic digestion unit by codigestion. Various SS-OFMSW samples were collected from canteens, supermarkets, restaurants, households, fruit-vegetable markets and bakery shops. The substrates characterization was carried out getting traditional chemical-physical parameters, performing elemental analysis and measuring fundamental anaerobic digestion macromolecular compounds such as carbohydrates, proteins, lipids and volatile fatty acids. Biochemical methane potential (BMP)tests were conducted at mesophilic temperature both on single substrates and in codigestion regime with different substrates mixing ratios. The maximum methane yield was observed for restaurant (675NmlCH4/gVS)and canteens organic wastes (571 and 645NmlCH4/gVS). The best codigestion BMP test has highlighted an increase of 47percent in methane production respect sewage sludge digestion.
Keywords: ANAEROBIC CO-DIGESTION; BIOCHEMICAL METHANE POTENTIAL; BMP; DIFFERENT SUBSTRATES; MACROMOLECULAR COMPOUNDS; MESOPHILIC TEMPERATURE; OFMSW; ORGANIC FRACTION OF MUNICIPAL SOLID WASTES